Urovagina in Dairy Cattle: A Clinical Overview - Gautam, Gokarna (Journal of Agriculture and Forestry University, 2026)
Urovagina is the pathological condition in which the urine accumulates into the floor of cranial vagina. Its prevalence in dairy cows and impact on fertility has been sparsely investigated in comparison to that in mare. The cases of urovagina in dairy cows have been increasing and this condition appears to be one of the important causes of infertility through conception failure, repeat breeding and embryonic loss. The prevalence of clinically relevant urovagina in Holstein cows across various countries ranged from 3.1% to 15.4%. Major risk factors of urovagina involve multiple parturition, low body condition score, horizontal vulva, cranio-ventral pelvic displacement and postpartum endometritis. Mild cases can be managed by improving body condition and vaginal douching, whereas moderate to severe cases often require surgical correction, such as urethral extension, flap-based techniques, or vestibulovaginal cerclage. Early diagnosis and targeted intervention are critical to restore normal urine flow, prevent uterine damage, and improve conception rates, thereby enhancing overall reproductive efficiency in affected cows. This article highlights the etiology, risk factors, prevalence, diagnosis and impact of urovagina and its treatment approach in dairy cattle and its management.